Sex is a funny word : a book about bodies, feelings, and YOU - Silverberg, Cory; Smyth, Fiona (Seven Stories Press, 2015)
"A comic book for kids that includes children and families of all makeups, orientations, and gender identies, Sex Is a Funny Word is an essential resource about bodies, gender, and sexuality for children ages 8 to 10 as well as their parents and caregivers. Much more than the "facts of life" or "the birds and the bees," Sex Is a Funny Word opens up conversations between young people and their caregivers in a way that allows adults to convey their values and beliefs while providing information about boundaries, safety, and joy. The eagerly anticipated follow up to Lambda-nominated What Makes a Baby, from sex educator Cory Silverberg and artist Fiona Smyth, Sex Is a Funny Word reimagines "sex talk" for the twenty-first century."--